Investigation of structural and electrical properties of ITO thin films and correlation to optical parameters extracted using novel method based on PSO algorithm - Amrani, Rachid; Garoudja, Elyes; Lekoui, Fouaz; Filali, Walid; Neggaz, Hamid; Djebeli, Yacine Adlane; Henni, Laid; Hassani, Salim; Kezzoula, Faouzi; Oussalah, Slimane; Al mashary, Faisal; Henini, Mohamed (Bulletin of materials science, 2023)
Thermally annealed DC sputtered indium tin oxide (ITO) thin films were investigated for improvement in properties. The structural and optoelectronic characteristics of as-grown and air annealed films were studied and correlated to the film deposition time. Raman spectroscopy analysis showed low crystalline quality films for as-grown films and were significantly improved after annealing. X-ray diffraction analysis confirmed the crystallinity of samples with (222) preferential orientation. The 30-min ITO films showed a peak at (400). The films optical study shows an increased transmittance (in the transparency region) with decreasing deposition time, yielding a high transparency of 90% for the 5- and 15-min ITO films annealed at 400°C. The films thickness and optical constants were determined from optical transmission only without interference fringe using a novel method based on particle swarm optimization (PSO) algorithm. The absorption coefficient and calculated refractive index decreased with increasing deposition time and their value reduced further after annealing treatment. The 30-min ITO films showed a comparable low resistivity of 4 × 10 −3 Ω cm before and after annealing as determined by Hall effect measurements. This observation confirms their non-sensitivity to the oxygen post-contamination that resulted from (400) orientation. A shift of the absorption edge towards shorter wavelengths accompanied with an increase in the optical bandgap before and after annealing with decreasing thickness were observed. We have demonstrated that the optical parameters such as the optical gap depend mainly on the electrical parameters such as the carrier concentration.